Deep Eutectic Solvents and Pharmaceuticals - Sónia N. Pedro (Encyclopedia, 2021)
Deep eutectic solvents (DES) are eutectic mixtures that present a deviation from the ideal thermodynamic solid–liquid phase behavior, where a significant depression in the melting temperature occurs. If properly designed and chosen, DES may be liquid at room and the human body’s temperatures and display a biocompatible character, thus representing relevant options in the pharmaceutical field. Accordingly, DES have been studied as alternative solvents or in formulations of pharmaceuticals to improve their solubility and stability. Depending on the DES components, these mixtures might exhibit interesting biological activities compatible with several applications. The use of DES as functional agents or as novel liquid forms of active pharmaceutical ingredients (API-DES) with the goal of improving bioavailability, permeability and therapeutic efficacy of a given API stands as alternative strategies in the pharmaceutical field for drug delivery purposes.